A SISTEM PAKAR DIAGNOSA HAMA DAN PENYAKIT TANAMAN KELAPA SAWIT BERBASIS ANDROID MENGGUNAKAN METODE CERTAINTY FACTOR - Adrian Terasta Ginting; Damar Nucahyono; M. Farman Andrijasa (Journal of Informatics and Computing (RANDOM), 2022)
The current gadget is a device that has reached almost the majority of the community, including farmers. By implementing an expert system, it is hoped that farmers will have no difficulty in determining pests and diseases on their oil palm plants. An expert system is a program that will model the ability to solve problems like an expert so that efficiency and effectiveness are obtained in getting a solution to existing problems. The increase in oil palm yields certainly cannot be separated from good productivity, the increase will decrease if many oil palm plants are attacked by disease. In this study the certainty factor method was applied to accommodate the level of expert confidence so that it could be applied to create an Expert System for Diagnosing Pests and Diseases of Oil Palm Plants using the certainty factor method and obtained the percentage of confidence values for pests or diseases and their control solutions.